ANALISIS NILAI TAMBAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI TEKNIS PADA AGROINDUSTRI KERIPIK APEL DI KOTA BATU - Sofi Amaliyah Wulansari (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
Abstract This study aims to: (1) know how much the value of R / C Ratio and income in the apple chips agro-industry in Batu City. (2) knowing the great value added to the apple chips agroindustry in Batu City. (3) knowing the factors which influence technical efficiency in apple chips agroindustry in Batu City. The location of the study was conducted purposively in Batu City. The number of samples was determined by 30 producers of apple chips using a simple random method. The data analysis used income analysis, analysis of added value by hayam methods and analysis of frontier production functions by Maximum Likelihood Estimation (MLE) method. The results of this study showed that the profits obtained in one production process amounted to Rp. 889,563 with an R / C ratio of 1.50, which means that the apple chips industry is worth being bussiness. The added value which obtained from 1 kg of raw material of apples used for apple chips will provide added value of Rp. 16,316.7. Production factors have a significant effect on apple chips production is raw material and labor. While some socio-economic factors that significantly influenced are age, experience and income. Keywords: apple chips, added value, technical efficiency of agroindustry.